2015
DOI: 10.1111/anu.12346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary components on the gut microbiota of aquatic animals. A never‐ending story?

Abstract: It is well known that healthy gut microbiota is essential to promote host health and well‐being. The intestinal microbiota of endothermic animals as well as fish are classified as autochthonous or indigenous, when they are able to colonize the host's epithelial surface or are associated with the microvilli, or as allochthonous or transient (associated with digesta or are present in the lumen). Furthermore, the gut microbiota of aquatic animals is more fluidic than that of terrestrial vertebrates and is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
418
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 522 publications
(432 citation statements)
references
References 529 publications
(462 reference statements)
6
418
0
8
Order By: Relevance
“…Previous studies also support the key roles of feeding habit in determining the intestinal microbiota of young and adult fish [17, 59]. Thus, the composition of gut microbiota is closely related to fish feeding habit in all the developmental stages since the fish starts to consume the aliments from environment [2, 11]. Interestingly, we observed a high similarity in the compositions of gut microbiota at stages ZS3 and TS1 (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies also support the key roles of feeding habit in determining the intestinal microbiota of young and adult fish [17, 59]. Thus, the composition of gut microbiota is closely related to fish feeding habit in all the developmental stages since the fish starts to consume the aliments from environment [2, 11]. Interestingly, we observed a high similarity in the compositions of gut microbiota at stages ZS3 and TS1 (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…In order to show the whole picture of changes induced by the PBM diets, further work, especially the histological examination of the tench intestine, is required. One of the interesting tasks to accomplish is to define whether and to what extent various dietary supplements influence the population level and the composition of bacteria in the gastrointestinal tract of tench, as numerous studies have shown for other species (Ringø et al, 2016;Sui et al, 2016). The results of the present study complement the results of previous studies investigating the effects of the PBM diet on numerous features in tench.…”
Section: R Panicz Et Alsupporting
confidence: 65%
“…However, other studies have shown that Firmicutes account for >90% of the gut microbiota in Nile tilapia (Standen et al, 2015). Discrepancies in microbiota composition can be due to how the animals were raised and fed, the analysis of autochthonous versus allochthonous bacterial communities, the methodology used for DNA extraction, and sequencing platform and pipeline data analysis (Ringo et al, 2015, Larsen et al, 2014b.…”
Section: Discussionmentioning
confidence: 99%